2020
DOI: 10.33462/jotaf.678764
|View full text |Cite
|
Sign up to set email alerts
|

Tarım Sektörünün Çevre Kirliliği Üzerindeki Etkisi: Türkiye Ekonomisi İçin Bir Eşbütünleşme ve Nedensellik Analizi

Abstract: Son yıllarda çevre kirliliği ve onu etkileyen temel faktörlerin doğru tespit edilebilmesi, önemli bir inceleme konusudur. Bu çalışmanın amacı, Türkiye'de tarım sektörü ve çevre kirliliği arasındaki ilişkiyi 1968-2016 dönemi için araştırmaktır. Literatürde tarım sektörü ve çevre kirliliği arasındaki ampirik ilişki hakkında bir fikir birliği bulunmamaktadır. Bu nedenle çalışma hem literatüre katkı sağlamakta hem de gelecekteki çalışmalar için önemli bir kanıt sunmaktadır. Çalışmada tarımın belirleyicileri olarak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In such a context, (Çetin et al, 2021) found that renewable energy consumption decreases CO 2 emissions in Turkey. The same conclusion was again reached by (Çeti̇n et al, 2020) for Turkey in the presence of the role of the agriculture sector. Moreover, the environmentally harmful role of fossil fuels is outlined by (Magazzino et al, 2021; Sümerli Sarıgül & Altay Topcu, 2021).…”
Section: Literature Reviewsupporting
confidence: 77%
“…In such a context, (Çetin et al, 2021) found that renewable energy consumption decreases CO 2 emissions in Turkey. The same conclusion was again reached by (Çeti̇n et al, 2020) for Turkey in the presence of the role of the agriculture sector. Moreover, the environmentally harmful role of fossil fuels is outlined by (Magazzino et al, 2021; Sümerli Sarıgül & Altay Topcu, 2021).…”
Section: Literature Reviewsupporting
confidence: 77%
“…The outcome of agriculture has a positive and significant effect on Carbon footprint from liquid with a 36.75 % increase in environmental degradation and a negative impact on Carbon footprint in the total emissions by 19.12 %[54] Structural fracture unit root tests, ARDL, Toda-Yamamoto causality test/Turkey 1968-2016 There is cointegration. In the long term, Carbon footprint is diminished by agriculture value-added and agricultural land.…”
mentioning
confidence: 99%